Offshore wind turbines: simulation of multibody drive train, interaction with fractional-order control and full-power converter - Melício, Rui (2013)
his paper is on offshore wind energy conversion systems with full-power converter and permanent magnet synchronous generator. The new drive train considered in this paper corresponds to a five-mass model and the resistant stiffness torque (structure and tower) in the deep water due to the moving surface elevation. Also, a multilevel converter and a fractional-order control strategy are considered. Simulation studies are carried out in order to adequately assess the harmonic content of the energy injected into the electric grid. Conclusions are duly drawn.